1990
DOI: 10.1152/ajpendo.1990.259.6.e844
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the process of sodium-calcium exchange in pancreatic islet cells

Abstract: Na(+)-Ca2+ exchange may play a role in Ca2+ extrusion from the pancreatic B-cell. The characteristics of the process working in its reverse mode were examined in normal rat pancreatic islet cells. Isosmotical replacement of extracellular Na+ by sucrose induced a concentration-dependent increase in 45Ca uptake, displaying a pharmacological sensitivity compatible with an uptake mediated by Na(+)-Ca2+ exchange. Glucose, up to 2.8 mM, stimulated reverse Na(+)-Ca2+ exchange. Likewise, membrane depolarization activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…3 and 4). In previous studies, we showed that this maneuver stimulated Ca 2ϩ entry and [Ca 2ϩ ] i rise in pancreatic ␤-cells selectively by Na/Ca exchange (reverse mode) (10,11). Figure 3 illustrates the time courses of Na ϩ i -dependent Ca 2ϩ uptake in control and NCX1.7-transfected cells.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…3 and 4). In previous studies, we showed that this maneuver stimulated Ca 2ϩ entry and [Ca 2ϩ ] i rise in pancreatic ␤-cells selectively by Na/Ca exchange (reverse mode) (10,11). Figure 3 illustrates the time courses of Na ϩ i -dependent Ca 2ϩ uptake in control and NCX1.7-transfected cells.…”
Section: Resultsmentioning
confidence: 92%
“…For the measurement of the effect of glucose, the media contained glucose (1.1 or 11.1 mmol/l) without nifedipine. The method used for the measurement of 45 Ca uptake has been described previously (10). Cytosolic Ca 2؉ concentration measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, BRIN-BD11 cells were preincubated in 1 ml of a nonradioactive solution for 30 min and then incubated for 90 min in 1 ml of the same medium, which also contained 10 Ci/ml 45 Ca 2ϩ . At the end of the incubation, the cells were separated from the incubation medium using a combined lanthanum and oil technique (27). Intracellular Ca 2؉ concentration measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The methods used to measure 45 Ca uptake in intact islets and insulin release from perifused islets are described elsewhere [17][18][19][20]. Insulin was assayed using an ELISA kit (Mercodia, Uppsala, Sweden).…”
Section: Pmca2mentioning
confidence: 99%